Her unfearing mind : women and Muslim laws in Bangladesh - Kamal, Sultana (Ain o Salish Kendro, 2001)
Report of the Research Project on Women and Law in the Muslim World conducted by the international solidarity network of Women Living Under Muslim Laws.